Skip to main content
Solve for x
Tick mark Image
Graph

Similar Problems from Web Search

Share

\frac{57.5\left(-x+1\right)^{2}}{57.5}=\frac{82.2}{57.5}
Divide both sides of the equation by 57.5, which is the same as multiplying both sides by the reciprocal of the fraction.
\left(-x+1\right)^{2}=\frac{82.2}{57.5}
Dividing by 57.5 undoes the multiplication by 57.5.
\left(-x+1\right)^{2}=\frac{822}{575}
Divide 82.2 by 57.5 by multiplying 82.2 by the reciprocal of 57.5.
-x+1=\frac{\sqrt{18906}}{115} -x+1=-\frac{\sqrt{18906}}{115}
Take the square root of both sides of the equation.
-x+1-1=\frac{\sqrt{18906}}{115}-1 -x+1-1=-\frac{\sqrt{18906}}{115}-1
Subtract 1 from both sides of the equation.
-x=\frac{\sqrt{18906}}{115}-1 -x=-\frac{\sqrt{18906}}{115}-1
Subtracting 1 from itself leaves 0.
-x=\frac{\sqrt{18906}}{115}-1
Subtract 1 from \frac{\sqrt{18906}}{115}.
-x=-\frac{\sqrt{18906}}{115}-1
Subtract 1 from -\frac{\sqrt{18906}}{115}.
\frac{-x}{-1}=\frac{\frac{\sqrt{18906}}{115}-1}{-1} \frac{-x}{-1}=\frac{-\frac{\sqrt{18906}}{115}-1}{-1}
Divide both sides by -1.
x=\frac{\frac{\sqrt{18906}}{115}-1}{-1} x=\frac{-\frac{\sqrt{18906}}{115}-1}{-1}
Dividing by -1 undoes the multiplication by -1.
x=-\frac{\sqrt{18906}}{115}+1
Divide \frac{\sqrt{18906}}{115}-1 by -1.
x=\frac{\sqrt{18906}}{115}+1
Divide -\frac{\sqrt{18906}}{115}-1 by -1.
x=-\frac{\sqrt{18906}}{115}+1 x=\frac{\sqrt{18906}}{115}+1
The equation is now solved.